2017
DOI: 10.1021/acs.macromol.7b01369
|View full text |Cite
|
Sign up to set email alerts
|

Hydration and Mobility of Poly(ethylene oxide) Brushes

Abstract: Poly­(ethylene oxide) (PEO) hydration is an important factor determining brush properties and application efficacy. Using atomistic molecular dynamics simulations, we investigate hydration, static, and dynamic properties of PEO brushes on gold surface as functions of grafting density, σ. We found that at lower grafting densities PEO is well-hydrated except for the surface vicinity where we observe PEO adsorption substituting for the water layering. In pure THF or mixed THF/water solvent, there is no PEO adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(86 citation statements)
references
References 48 publications
(140 reference statements)
4
82
0
Order By: Relevance
“…8 The intriguing properties of PEO in water were already considered in previous simulation studies using different force fields and degree of coarse-graining. [9][10][11][12][13] Recently, Dahal and Dormidontova 14,15 have studied the hydration, static and dynamic properties of PEO chains both in aqueous solutions and grafted to the surface using atomistic molecular dynamics simulations.…”
Section: Introductionmentioning
confidence: 99%
“…8 The intriguing properties of PEO in water were already considered in previous simulation studies using different force fields and degree of coarse-graining. [9][10][11][12][13] Recently, Dahal and Dormidontova 14,15 have studied the hydration, static and dynamic properties of PEO chains both in aqueous solutions and grafted to the surface using atomistic molecular dynamics simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Still, the theory of brushes as kinetic barriers is hard to verify experimentally. This is mainly because regardless of whether protein adsorption is detected or not for a given system, the role of potential polymer-surface interactions outcompeting the protein adsorption 7 (equilibrium prevention) cannot be distinguished from the kinetic barrier effect. For instance, although surface plasmon resonance (SPR) can confirm qualitatively that brushes have protein excluding properties, [8][9][10] it does not provide the concentration profile perpendicular to the surface.…”
mentioning
confidence: 99%
“…Although QCM‐D cannot differentiate between the trapped and solvated H 2 O molecules, the hydration behavior at these low densities are not further commented in our current study. Dahal et al . employed atomistic molecular dynamic simulations and observed a similar decrease in the number of hydrogen bonds per monomer and an increase in the residence time for hydrogen‐bound H 2 O in the hydration shell with an increase in the density of the poly(ethylene oxide) chains on the surface.…”
Section: Resultsmentioning
confidence: 84%
“…Recent studies, however, have also shown that the local solvation structures influence the structural transitions in chains leading to chain stiffening and enhanced film rigidity . The interdependence of chain flexibility and the amount of hydrated H 2 O on brush properties, especially for PEG and PMOXA brushes have not been studied in detail previously.…”
Section: Introductionmentioning
confidence: 99%